The Effect of Innovation, Entrepreneurship and Business Development on the Economic Independence of Muslims - Sono, Moh Gifari; Rijal, Syamsu; Devi, Erwina Kartika; Utami, Eva Yuniarti (West Science Islamic Studies, 2024)
This research investigates the impact of innovation, entrepreneurship, and business development on the economic independence of Muslims in Indonesia through a quantitative analysis. A sample of 120 respondents representing diverse demographic backgrounds was surveyed, and Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed to analyze the data. The measurement model assessment confirmed the reliability and validity of the constructs, while the structural model estimation revealed significant positive relationships between innovation, entrepreneurship, business development, and economic independence. Hypothesis testing further validated these relationships, indicating that all three factors—innovation, entrepreneurship, and business development—have a significant positive effect on economic independence among Muslims in Indonesia. The findings underscore the importance of fostering innovation ecosystems, nurturing entrepreneurial talent, and creating conducive business environments to promote economic autonomy within the Muslim community. These insights have implications for policymakers, practitioners, and stakeholders seeking to design targeted interventions for inclusive economic development and sustainable growth in Indonesia.